Improving Student’s Writing Achievement Through Multiple Intelligences - Iwansyah Putra; Imam Sonhaji (Jurnal Penelitian)
The aim of this research was to find out whether there was a significant difference of students’ writing achievement before and after being taught through students’ multiple intelligences. The sample of the research was eleventh grade students of Islamic high school in Sekayu, Musi Banyuasin, South Sumatera. The research was conducted by applying quasi experimental in terms of pretest – posttest non- equivalent group design. The sample of this research was 62 science students. The Mean of posttest’s score was higher than pre-test. It means that there is an increase of students’ writing achievement after being taught through their multiple intelligences.